Air Formaldehyde Levels and Eye Irritation in Workers at Production Area of Wood Adhesive Factory in Surabaya - Mustika Ayu Raharyaningsih; R Azizah (JURNAL KESEHATAN LINGKUNGAN, 2017)
Formaldehyde is a chemical substance that has volatile and short-term effect characteristics, which can cause eye irritation. Exposure to formaldehyde in low levels can cause irritation to human eyes. The purpose of this research was to study the production process, air formaldehyde levels and eye irritation at Wood Adhesive Factory workers in Surabaya. This study was an observational study with cross sectional design and analyzed descriptively. The variables studied were levels of formaldehyde in the air and eye irritation of workers. Results showed that the average levels of formaldehyde in three areas of production (formalin, liquid adhesive, and powder adhesive production) was 0.2102 ppm and 12.5% of respondents experiencing eye irritation had age between 26-35 years, working period less than 10 years, length of work 7 hours per day, not wearing personal protective equipment safety glasses (spectacles) and had a habit of smoking. The factory had provided personal protective equipment safety glasses (spectacles), but 37.5% of the respondents did not wear personal protective equipment when they were working. Hence strict supervision regarding the use of personal protective equipment is needed, especially safety glasses (spectacles) so that workers are more obedient in wearing personal protective equipment and eye irritation to workers can be avoided.